DETERMINAN PENJUALAN DITINJAU DARI BIAYA PEMASARAN DAN IKLAN DAN PROMOSI PADA PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2022 - Jennifer Brooklin Mira; Herold Moody Manalu; Francis Hutabarat (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
Sales are the goal of every company, this study uses marketing costs and advertising and promotion as factors that influence sales in food and beverage sector companies on the Indonesia Stock Exchange. This research is quantitative and the research sample is 17 food and beverage companies on the Indonesia Stock Exchange from 2019-2022. The results showed that there was a significant influence between marketing costs and sales. The same thing is found that advertising and promotion have a significant effect on sales. Simutaneously found that both factors have significant results on sales.